Analysis of Multiple Correspondence Against Crimes in Sleman Regency - Widodo, E; Maggandari, R (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2021)
Crime is bad behavior, from social and religious norms and it makes psychology and economics harm. Stealing, ill-treatment, embezzlement, deception, deception/embezzlement, and adultery are the most crime in the last 9 months. Therefore, for identify the type of crime in the community we need a method to see the tendency of a category using multiple correspondence analysis methods. Analysis of multiple correspondences is one of the descriptive statistics that use to describe a pattern of relationships from contingency’s table with the aim of finding liability between categories. The results of the correspondence analysis are that the tendency of criminal suspect to be related to this types of crime of stealing and ill-treatment to be done by students or students less than 25 years old and were male, suspect of deception and adultery tends to be done by women over 40 years old and does not work, and suspect of embezzlement tends by workers and their ages around 25 to 40 years. The liability of the relation between criminal incidents and the types of crime is the types of crime of ill-treatment and adultery that are most prone to occur in shops with vulnerable hours 00:00-05:59 and 18:00-23:59.